Use of Generalized Regime Indicators when Evaluating Adaptive Reserve Coefficients by Active Power - N.Sh., Chemborisova; ., . (International Journal of Engineering and Technology, 2018)
To ensure the efficiency of the regime of electric power systems (EPS) most of the time should work near their physical limits, including the conditions of static aperiodic stability. To calculate the margin factors for active power corresponding to the existing scheme-operational situations (adaptive), when using the aggregate indicators of the mode in which the second derivatives are selected from the total active power losses in the network according to the controlled parameter. Safety factors allow you to separate the area "flow" modes, in which when equal to perturbing influences will have received a large response from areas of normal functioning.Â Â